Computational Science Educational Game on a Basic Algorithm for Grade 1 Students - Nongkunoi, Jutarat; Cholwithi, Nutchaya; Maneechod, Apisara; Prammanee, Noppadol; Lorphichian, Aekkarat (Mahachula Academic Journal, 2023)
The purposes of this research were to (1) develop computational science educational game on a basic algorithm for grade 1 students with a level of good quality, (2) compare pre-test scores before computational science educational game on a basic algorithm and post-test scores after computational science educational game on a basic algorithm of all students, (3) study the students’ level of satisfaction from computational science educational game on a basic algorithm. The sample group used in this research were students currently studying in Grade 1 Semester 2 Academic Year 2021 at Thanyasitthisin School, the focus sample group included 30 students in Grade 1/1. The results of the research showed that (1) the assessment by content experts on computational science educational game on a basic algorithm for grade 1 students was at the highest level (= 4.61) and the assessment by multimedia specialists was at a high level (= 4.38), (2) the pre-test scores before computational science educational game on a basic algorithm and post-test scores after computational science educational game on a basic algorithm on a basic algorithm for grade 1 students had statistically significant differences at the 0.05 level; pre-test scores (= 5.03), post-test scores (= 7.70), where the average post-test scores were 2.67 points higher than the pre-test scores. (3) The results of the students’ level of satisfaction from computational science educational game on a basic algorithm for grade 1 students, their satisfaction was at the highest level of satisfaction (= 4.53).